2005
DOI: 10.1510/icvts.2004.103424
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the modified maze procedure for atrial fibrillation combined with rheumatic mitral valve disease using cryoablation

Abstract: This study evaluated the mid-term results of the modified maze procedure using cryoablation for treating atrial fibrillation associated with rheumatic mitral valve disease. Between March 2000 and February 2004, 177 consecutive patients underwent the modified maze procedure using cryoablation concomitant with mitral valve surgery, were divided into the modified Cox-Maze III (group CM, n=88), modified Kosakai-Maze (group KM, n=63) and left atrial maze (group LA, n=26) procedures. Postoperative and follow-up resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For more than a decade, the maze procedure has evolved to become the most successful surgical treatment for medically refractory AF [3,4,[12][13][14][15][16]. However, up to the present, several studies have shown diverse outcomes of the maze procedure in curing AF associated with rheumatic mitral valve disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than a decade, the maze procedure has evolved to become the most successful surgical treatment for medically refractory AF [3,4,[12][13][14][15][16]. However, up to the present, several studies have shown diverse outcomes of the maze procedure in curing AF associated with rheumatic mitral valve disease.…”
Section: Discussionmentioning
confidence: 99%
“…1). The details of the operative technique of our modified maze procedure were described previously [13]. Cryoablation using a dual-probe cardiac cryosurgical system (Frigitronics, Cooper Surgical, Shelton, CN) was applied for 90 s to 2 min at À60 8C according to the thickness of the atrial wall.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…Despite no significant improvements in 5-year overall survival rate, this approach can be considered a safe palliative treatment for unresectable pancreatic cancer. Cryoablation is also effective in reducing instances of post-operative bleeding (from 6-8% to 3.4%) during a maze procedure for atrial fibrillation 92 . A combination of laparoscopic surgery and cryoablation was shown to be feasible in select patients to treat multi-visceral tumors, although further work is needed to test its viability in a wider patient range 90 .…”
Section: Combination Cryoablation Cancer Therapiesmentioning
confidence: 99%